Laminated Veneer Lumber (LVL) sengon: an innovative sustainable building material in Indonesia - Awaludin, Ali; Shahidan, Shahiron; Basuki, Achmad; Mohd Zuki, Sharifah Salwa (Penerbit UTHM, 2018)
Laminated Veneer Lumber (LVL) is recently available in Indonesian markets. The veneers are majority from Sengon wood (Paraserianthes falcataria), which is a fast-growing timber species native to Indonesia. Their use in practice is limited to non-structural components since Sengon wood species has low engineering properties and less resistance to termite attacks. The LVL production introduced few years ago has significantly improved both mechanical properties and durability as well as has expanded its utilization into various structural components. This remarkable improvement has made LVL Sengon wood as an innovative sustainable building materials in Indonesia. This paper summarized a series of authors’ work conducted since couple years ago to initiate the utilization of LVL Sengon in structural components such as shear walls and floor systems as parts of a project to develop its design standard. In addition, creep behavior of this LVL is also highlihgted here as this phenomenon is essential for designers and engineers to anticipate their designs within their service life. In particular, the test results showed that addition of diagonal members increased both racking resistance and equivalent viscous damping ratio of the developed LVL shear walls. And the LVL floor model which is composed of built-up box joists and plywood sheathing remained liniear-elastic under bearing load up to 18.75 kN/2 .